2008
DOI: 10.1002/app.26125
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induced graft copolymerization of vinyl monomers and their binary mixture onto rayon fibre

Abstract: Ethyl acrylate (EA), Vinyl imidazole (VI), and their binary mixture have been copolymerized onto rayon in aqueous medium by mutual method using g-radiation. The graft yield has been determined as a function of different reaction parameters such as total dose, concentration of vinyl monomers, and amount of water. Effect of surfactant (1-octane sulfonic acid, sodium salt) has been studied on the percentage of grafting of EA, VI, and (EA þ VI). A plausible mechanism has been suggested to explain the observed beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Intensive studies have been carried out on the graft copolymerization of cellulosic polymers with suitable hydrophobic monomers to introduce desired functionalities into the cellulosic backbone, so as to overcome the sensitivity of cellulosic fibers towards water/moisture absorption and poor chemical resistance and thus to improve the existing physicochemical properties of the cellulosic polymers (Bashar, Khan, & Idriss Ali, 1995;Kaur, Kumar, & Sharma, 2010;Rattan, Maitra, Misra, & Kaur, 2008;Thakur, Thakur, & Gupta, 2013a). A biocide cellulose carbamate with antimicrobial properties was prepared by impregnating the fibers in aqueous thiourea solution and subsequently grafting with acrylonitrile (Dahou, Ghemati, Oudia, & Aliouche, 2010).…”
Section: Cellulosementioning
confidence: 99%
“…Intensive studies have been carried out on the graft copolymerization of cellulosic polymers with suitable hydrophobic monomers to introduce desired functionalities into the cellulosic backbone, so as to overcome the sensitivity of cellulosic fibers towards water/moisture absorption and poor chemical resistance and thus to improve the existing physicochemical properties of the cellulosic polymers (Bashar, Khan, & Idriss Ali, 1995;Kaur, Kumar, & Sharma, 2010;Rattan, Maitra, Misra, & Kaur, 2008;Thakur, Thakur, & Gupta, 2013a). A biocide cellulose carbamate with antimicrobial properties was prepared by impregnating the fibers in aqueous thiourea solution and subsequently grafting with acrylonitrile (Dahou, Ghemati, Oudia, & Aliouche, 2010).…”
Section: Cellulosementioning
confidence: 99%
“…SPF fibre has smooth and homogeneous surfaces which get swollen on benzoylation. Graft copolymerization resulted in the rough and heterogeneous surfaces due to incorporation of poly (MMA) chains [30]. The increase in roughness further prompts sorption as it enhances trapping and physical adsorption of oil on surface of sorbent.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…In addition to the irradiation parameters, the DOG is also influenced by the feed monomer and comonomer ratio. [60][61][62][63][64][65][66][67] Earlier studies suggested that comonomers such as acrylic acid (AA), methacrylic acid (MA), and glycidyl methacrylate (GMA) (Fig. 5D) had a certain influence on the adsorption performance of uranium adsorbents.…”
Section: Strategies For Improving the Adsorption Abilitymentioning
confidence: 99%